2015
DOI: 10.3389/fnhum.2015.00323
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in sleep spindles characteristics during daytime recovery following a 25-hour sleep deprivation

Abstract: Objectives: The mechanisms underlying sleep spindles (~11–15 Hz; >0.5 s) help to protect sleep. With age, it becomes increasingly difficult to maintain sleep at a challenging time (e.g., daytime), even after sleep loss. This study compared spindle characteristics during daytime recovery and nocturnal sleep in young and middle-aged adults. In addition, we explored whether spindles characteristics in baseline nocturnal sleep were associated with the ability to maintain sleep during daytime recovery periods in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…The age by condition interaction was a main focus of the study and was significant for N3%. The lower N3% increase in the older group in response to LSS agrees with what could be expected based on previous work on full‐sleep after total sleep loss (Cajochen et al ., ; Lafortune et al ., ; Rosinvil et al ., ). In addition, the reduction in N2% was lower in the older group, which seems logical because of the modest increase in N3% in that group; the two sleep stages normally interact because N3 is scored when the EEG amplitude exceeds criterion (75 μ V) and N2 when it falls below the criterion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The age by condition interaction was a main focus of the study and was significant for N3%. The lower N3% increase in the older group in response to LSS agrees with what could be expected based on previous work on full‐sleep after total sleep loss (Cajochen et al ., ; Lafortune et al ., ; Rosinvil et al ., ). In addition, the reduction in N2% was lower in the older group, which seems logical because of the modest increase in N3% in that group; the two sleep stages normally interact because N3 is scored when the EEG amplitude exceeds criterion (75 μ V) and N2 when it falls below the criterion.…”
Section: Discussionmentioning
confidence: 97%
“…One possible modifier of the response to LSS may be age, because older individuals have shorter total sleep time (TST), less sleep stage N3, less REM, and more stage N1 during full‐night sleep than young individuals (Bixler et al ., ; Moraes et al ., ; Ohayon et al ., ). Older individuals also show a somewhat lower N3 response to total sleep deprivation than younger ones (Cajochen et al ., ; Lafortune et al ., ; Rosinvil et al ., ). Delta power density decreases with age, while REM density is unaffected (Schwarz et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, SWS and REM sleep may reflect levels of depression (Riemann, Berger, & Voderholzer, ) or compensation after insufficient sleep (Ong, Lo, Gooley, & Chee, ). These potential causes may further be reflected in the percentages of different sleep stages and spindle activity (Rosinvil et al., ). Sleep spindles vary in their morphology, or form, as well as their function across development (Clawson, Durkin, & Aton, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that spindles have been shown to play a role in memory consolidation during sleep and that previous studies of acoustic stimulation of slow waves have found concomitant changes in spindles, we also examined spindle changes in this study. Automated spindle detection (spindles between 9 and 16 Hz) was performed on channel Fpz for all ON and OFF intervals for stim and sham by adapting previously published methods that have also been employed in older adults . Additional details are described in Data S1.…”
Section: Methodsmentioning
confidence: 99%